Where does professional education on digital libraries lead our new librarians - Liu, Yan Quan (International Conference on Asian Digital Libraries, 2003)
This study investigates the state of school education for digital libraries. For this study, a web survey was conducted of syllabi of courses on the subject of digital libraries. Similarities and differences on such subjects as teaching emphases, course outlines, textbooks and assignments were compared. The majority of classes now contain a "hands-on" element, a practical component of the course that requires that the students interact with digital libraries. Those students who have received practical experience with digital libraries, like those provided in the "hands-on" courses, are best served for future practice in the field of librarianship. © Springer-Verlag Berlin Heidelberg 2003.
0 citations (Crossref) [2023-10-31] tex.type: Proceedings paper
Keywords: Digital libraries; E-learning; Education; Practical experience; Professional education; School education; Students; Teaching; Web surveys; dept.ils